Self‐Assembling Decacyclene Triimides Prepared through a Regioselective Hextuple Friedel–Crafts Carbamylation1. Issue 5 (17th December 2012) - Pho, Toan V.; Toma, Francesca M.; Chabinyc, Michael L.; Wudl, Fred
<x xml:space="preserve">Abstract</x> Molecular electronics: A hextuple Friedel–Crafts carbamylation is reported in the synthesis of the electroactive decacyclene triimides (see picture). These triimides self‐assemble into different nanostructures through modification of the alkyl substituents and are promising n‐type materials for organic semiconducting devices.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>